Design of BWAT method development in diabetic foot ulcers patients in hospital: Action research - Dewi Hartinah; Blacius Dedi; Widiyaningsih Widiyaningsih (Universitas Aisyiyah Yogyakarta, 2023)
Diabetic foot ulcers (DFU) are one of the complications of diabetes that has a serious impact and requires high treatment costs. However, they can be prevented early through a series of assessments. The most recommended initial assessment method to determine the risk of complications is the BWAT Method. However, nurses’ BWAT method is still considered too long and complicated. In addition, the hospital also has a different handling program from the BWAT method, so it is necessary to develop the BWAT method and adjust this method to the SOP, which is expected to be more easily applied by nurses. This study aims to design the development of the Bates-Jensen Wound Assessment Tools (BWAT) method for DFU patients with the development of Hospital SOPs. The research method is qualitative action research, while data collection uses focus group discussion (FGD) on 10 participants determined through purposive sampling techniques, with minimum nurse criteria and a minimum length of work of 5 years. Data analysis using the Collaizi model expert judgment was given to three speakers to design SOPs for the BWAT method of wound assessment. The study results obtained four themes related to wound assessment in DFU patients and a draft SOP for wound assessment by developing the BWAT method for DFU patients who received treatment at the hospital. The SOP development trial found that with the same flow but with shorter language, the SOP is easier to understand and easier for nurses to implement; however, improvements are still needed from this SOP, namely in the form of additional evaluation items in the SOP that are expected to be used to improve communication between health care providers to facilitate the process of providing sustainable nursing services.